2022
DOI: 10.1371/journal.pclm.0000012
|View full text |Cite
|
Sign up to set email alerts
|

Urban climate-health governance: Charting the role of public health in large global city adaptation plans

Abstract: Over the last decade many large world cities have scaled up efforts at climate adaptation, a primary focus of which is protecting population health. With extreme weather disasters increasing worldwide, public health agencies are among local institutions under greatest stress; the Covid-19 pandemic has only heightened pressure on these agencies. Yet the limited literature examining adaptation actions across world cities suggest few, mainly high-income cities report health-related adaptation, while city public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The lack of inclusion of public health aspects in urban settings has been reported elsewhere [ 93 , 94 , 95 ]. For instance, a recent comparative review, which aimed to characterize the public health role in the adaptation plans of 22 large cities pre-identified as highly health-adaptive, examined five health-associated adaptation activities as “promising practices” based on evidence synthesized from evaluation research and practical experience [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of inclusion of public health aspects in urban settings has been reported elsewhere [ 93 , 94 , 95 ]. For instance, a recent comparative review, which aimed to characterize the public health role in the adaptation plans of 22 large cities pre-identified as highly health-adaptive, examined five health-associated adaptation activities as “promising practices” based on evidence synthesized from evaluation research and practical experience [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of inclusion of public health aspects in urban settings has been reported elsewhere [ 93 , 94 , 95 ]. For instance, a recent comparative review, which aimed to characterize the public health role in the adaptation plans of 22 large cities pre-identified as highly health-adaptive, examined five health-associated adaptation activities as “promising practices” based on evidence synthesized from evaluation research and practical experience [ 95 ]. The five areas included: hazard and vulnerability mapping; extreme weather preparedness and response; extreme heat plans (including heat early warning); non-heat early warning (e.g., flooding or vector-borne diseases); and climate–health monitoring and outcome surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that when the public health sector is involved, climate adaptation outcomes may be better targeted towards those in greatest need. 45 , 46 Viewing agrobiodiversity through the lens of health can increase knowledge and awareness in the population and provide compelling reasons for behaviour change. Including health-linked urban agrobiodiversity indicators within climate adaptation plans may be especially relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient attention to public health in municipal climate adaptation planning has been reported in other studies. For example, the recent analysis of climate adaptation plans of 22 large cities in 14 countries, including 16 in high-income countries by[130] indicated that even "highly health-adaptive large cities report fairly modest public health engagement in climate adaptation plans, and very few seem to have integrated a health perspective across thematic or sectoral climate adaptation priorities" (p.14).…”
mentioning
confidence: 99%